Increased nuchal translucency thickness and risk of neurodevelopmental disorders. (5th April 2017) - Hellmuth, S. G.; Pedersen, L. H.; Miltoft, C. B.; Petersen, O. B.; Kjærgaard, S.; Ekelund, C.; Tabor, A.
ABSTRACT: Objective: To investigate the association between fetal nuchal translucency (NT) thickness and neurodevelopmental disorders in euploid children. Methods: This study included 222 505 euploid children who had undergone routine first‐trimester screening during fetal life. Children were divided according to prenatal NT into three groups: NT < 95 th percentile ( n  = 217 103 (97.6%)); NT 95 th –99 th percentile ( n  = 4760 (2.1%)); and NT > 99 th percentile ( n  = 642 (0.3%)). All children were followed‐up to a mean age of 4.4 years. Information on diagnoses of intellectual disability, autism spectrum disorders (ASD), cerebral palsy, epilepsy and febrile seizures was obtained from national patient registries. Results: There was no excess risk of neurodevelopmental disorders among euploid children with first‐trimester NT 95 th –99 th percentile. For children with NT > 99 th percentile, there were increased risks of intellectual disability (odds ratio (OR), 6.16 (95% CI, 1.51–25.0), 0.31%) and ASD (OR, 2.48 (95% CI, 1.02–5.99), 0.78%) compared with children with NT < 95 th percentile (incidence of 0.05% for intellectual disability and 0.32% for ASD), however, there was no detected increase in the risk of cerebral palsy (OR, 1.91 (95% CI, 0.61–5.95), 0.47%), epilepsy (OR, 1.51 (95% CI, 0.63–3.66), 0.78%) or febrile seizures (OR, 0.72 (95% CI, 0.44–1.16), 2.65%). Conclusions: In a large unselected cohort of euploid children, there was no increased risk of neurodevelopmental disorders among those with a first‐trimester NT 95 th –99 th percentile. Among euploid children with first‐trimester NT > 99 th percentile, there were increased risks of intellectual disability and ASD, but the absolute risk was reassuringly low (< 1%). Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations. This article has been selected for Journal Club. Clickhere to view slides and discussion points. Ultrasound Obstet Gynecol 2017; 49: 564–564